Hubungan Penerapan Program Cerdik dengan Self Care pada Pasien Diabetes Melitus di Puskesmas Bunta Kabupaten Banggai Sulawesi Tengah - Sri Yulianti; Maharani Farah Dhifa dg Masikki; Abd Gani Baeda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Diabetes Mellitus is a progressive chronic disease that signed by body metabolism impairment of carbohydrates, protein, and fat, which could lead to hyperglycemia. DM diseases are mostly recognized as a silent killer disease that could kill people softly. DM complications include heart disease, stroke, kidney failure, amputation, and even death. In the prevention of DM disease need, each person's self-esteem by diabetes self-management should have certain good knowledge and skill to control it called Self-care. CERDIK is the government's program to support DM patients in performing self-care in their daily implementation. The research aims to obtain the association of the CERDIK program with self-care for diabetes mellitus patients. The total population is 120 people, and the sampling is only 43 respondents. The research phase starts from preparation and implementation until the completion of the research report. This research used quantitative research with a Cross-Sectional approach. CERDIK program as an independent variable showed that most of the respondents, 24 (55,8%), said that the CERDIK program had been implemented, and self-care for diabetes mellitus patients as a dependent variable has 27 respondents (62,8%). The result used chi-square test with p-value = 0,000. Because of the p-value < 0,05, there is an association between CERDIK Program With self-care Toward Diabetes Mellitus patients.